Sexual orientation knowledge and attitudes and its association with therapy satisfaction among lesbian, gay, and bisexual + Hispanic Puerto Ricans - Caleb Esteban; Margarita Francia-Martínez; Miguel Vázquez-Rivera; Frances Crespo; Taysha Bruno-Ortiz; Aquiria M. Santiago-Ortiz; Alfonso Martínez-Taboas (BMC Public Health, 2023)
Abstract This study aimed to examine the difference in therapy satisfaction between lesbian, gay, and bisexual + (LGB +) individuals and heterosexual individuals, and to identify the association between therapy satisfaction and the perception of knowledge and attitudes of their last therapist among the LGB + participants. Through an exploratory design with a comparative group, 125 LGB + and 75 heterosexual participants were recruited online by availability. Results indicate that the participants’ sexual orientation has no significant relation on therapy satisfaction. However, there was a significant positive association between satisfaction with therapy and the LGB + participants’ perception that their therapist demonstrated knowledge and positive attitudes. This research highlights the importance for continuous education and curriculum efforts on LGB + issues.